FACTORS AFFECTING TEACHER PERFORMANCE DURING THE COVID 19 ERA (MADRASAH IBTIDAIYAH CASE STUDY SOUTH JAKARTA) - Eva Fadhila Hanifa Luqman; Aslam Mei Nur Widigdo (Dinasti Publisher, 2021)
The purpose of this study is to find out the factors that affecting teacher performance during the era of covid 19 (case study Madrasah Ibtidaiyah South Jakarta). The research method used is a quantitative approach with causal research. The research population is 96 teachers in Madrasah Ibtidaiyah Negeri, Jagakarsa Subdistrict, South Jakarta City. Sampling technique is nonprobability sampling with saturated sampling technique so that the sample number of 96 teachers. Research data is primary data obtained by distributing questionnaires. Quantitative data analysis methods use multiple linear regression methods. The analysis tool used is SPSS version 26.0. The results of the F test showed that competence, communication, creativity and work environment had a positive and significant influence on teacher performance. The results of the t test on each variable showed that competence had no effect on teacher performance, communication had a significant and positive effect on teacher performance, creativity had a significant and positive effect on teacher performance and the work environment had no effect on teacher performance. Based on the results of the analysis, the performance of teachers during the covid 19 era can be maximized through the improvement of the creative process of creativity during the implementation of the learning process.